A Study Of Fundamental Right To Property And The Constitutional Objectives For India's Socio- Economic Development: Examining the Impact of Socioeconomic Goals on the Right to Property in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The researcher's goal here is to understand how the Constitution's socioeconomic goalsweakened the right to private property. The original intention of the right to property was to safeguardindividual property from tyrannical government. Multiple laws governing ownership are now in effect, bothat the federal and state levels. The constitutional goals for India's social and economic structure havebeen translated into law. These laws have been challenged in court, and the resulting animosity overproperty rights is palpable. While there have been calls to do away with property rights altogether, othershave argued that protecting private property is crucial to maintaining a functioning democracy. The Stateinitially watered down the Fundamental Right to Property through successive Constitutional amendmentsbefore reducing it to a mere constitutional right.